Enhancing Educator Performance through Edupreneurship in International Baccalaureate Programs - Lubis, Nada Shofa; Hanafi, Syadeli; Hidayat, Sholeh (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study investigates the impact of the International Baccalaureate (IB) curriculum on enhancing educator performance and commitment, focusing on the unique mediating role of curriculum effectiveness through Organizational Citizenship Behaviour (OCB), Learning Agility (LA), and Synergy (S). The research, conducted across three IB-certified Islamic schools, utilizes Structural Equation Modelling (SEM) to analyze data from 325 educators, uncovering how curriculum effectiveness fosters work commitment by strengthening OCB and Learning Agility. In the Background, the study highlights the global importance of quality education as outlined in SDG 4 (Quality Education), emphasizing the role of educators in delivering this goal. The Method involves a quantitative approach using SEM to assess the relationship between OCB, LA, Synergy, and educator commitment. The Object of this study is the IB curriculum effectiveness in fostering a high performance teaching environment. The Result indicates that OCB is the most influential factor, followed by Learning Agility, underscoring the IB curriculum capacity to enhance educator performance. Furthermore, the integration of SDG 4 within this research demonstrates how the IB curriculum supports educators in adapting to a globalized and evolving educational landscape. In Conclusion, the study suggests that enhancing structured support for OCB and agility within the IB curriculum can significantly elevate educator commitment and performance, ultimately contributing to the broader goal of SDG 4 ensuring inclusive, equitable, and quality education for all.